1997
DOI: 10.1038/ki.1997.245
|View full text |Cite
|
Sign up to set email alerts
|

Activation of renin synthesis is dependent on intact nitric oxide production

Abstract: The present study investigated whether or not nitric oxide (NO) synthesis mediates mechanisms regulating activation of renin formation. Studies were performed on afferent arterioles freshly isolated from the rat kidney. We have shown previously that this preparation is a useful model to study regulation of renin synthesis and secretion. The expression of renin mRNA was assessed by ribonuclease protection assay, and total renin content and renin secretion by radioimmunoassay. In afferent arterioles isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
2
21
2
1
Order By: Relevance
“…These data indicate that the adenylyl cyclase-mediated mechanism regulating renin release is impaired when NO synthesis is inhibited. Tharaux et al (1997) reported that in afferent arterioles isolated from rats treated with ramipril, renin mRNA levels, total renin content, and renin secretion were increased compared with untreated controls, with the effect of ACE inhibition being abolished by L-NAME; similar data were found in the arterioles from furosemide-treated rats, suggesting that NO acts on renin activation by a mechanism independent of ANG II. The inhibitory effect of L-NAME on the activation of renin secretion was abolished when afferent arterioles were 80 treated with nicardipine, an L-type Ca 2ϩ channel blocker.…”
Section: Other Vasculaturessupporting
confidence: 68%
“…These data indicate that the adenylyl cyclase-mediated mechanism regulating renin release is impaired when NO synthesis is inhibited. Tharaux et al (1997) reported that in afferent arterioles isolated from rats treated with ramipril, renin mRNA levels, total renin content, and renin secretion were increased compared with untreated controls, with the effect of ACE inhibition being abolished by L-NAME; similar data were found in the arterioles from furosemide-treated rats, suggesting that NO acts on renin activation by a mechanism independent of ANG II. The inhibitory effect of L-NAME on the activation of renin secretion was abolished when afferent arterioles were 80 treated with nicardipine, an L-type Ca 2ϩ channel blocker.…”
Section: Other Vasculaturessupporting
confidence: 68%
“…Tuning of NO/ ET-1 balance also regulates the VSMC phenotype in vivo. 11 In contrast, other investigators did not observe increased levels of ET-1 mRNA 26,27 or peptide 28 in aortas of rats chronically treated with L-NAME. However, as pointed out in these previous reports, aortic ET-1 synthesis may not reflect alterations of ET-1 levels in renal resistance vessels.…”
Section: Discussionmentioning
confidence: 80%
“…11 Vascular preparations containing Ͼ90% of preglomerular vessels were retained for subsequent experiments. The protein vascular content was measured according to Bradford's method.…”
Section: Isolation Of Preglomerular Vesselsmentioning
confidence: 99%
“…Several in vitro studies provided evidence that NO might act as an inhibitor of renin release. 58,59 However, other in vitro observations 60 and experiments in isolated perfused kidneys 61 suggested that NO stimulates the synthesis and/or secretion of renin. In addition, several investigators reported decreased circulating renin in the chronic NOS inhibition model, 28,29,51,62,63 even in animals in which PRA was initially elevated by restricted dietary sodium intake 62 or reduction of renal perfusion pressure.…”
Section: Role Of the Rasmentioning
confidence: 99%